Noncirrhotic Portal Hypertension in Patients With Human Immunodeficiency Virus–1 Infection - Saifee, Sophia; Joelson, Dean; Braude, James; Shrestha, Roshan; Johnson, Mark; Sellers, Marty; Galambos, Michael R.; Rubin, Raymond A. (Clinical gastroenterology and hepatology, 2008)
Noncirrhotic portal hypertension (NCPH) is unusual in North American patients. This study characterized patients with NCPH and human immunodeficiency virus–1 (HIV-1) infection to identify potential risk factors for this association. Eleven consecutive patients from our urban hepatology clinic with HIV-1 infection and NCPH were the subject of this series. Case histories, including medication lists and laboratory data, were analyzed. Age at diagnosis was 51 ± 7 years. CD4 count was 303 ± 185 cells/mL, and HIV viral load was <75 copies/mL in 9 patients. Didanosine was the only medication taken by all patients; 10 each had taken lamivudine and zidovudine. In the 10 patients tested, 8 had at least 1 thrombophilic abnormality; 6 were deficient in protein S, and 2 had multiple abnormalities. Nodular regenerative hyperplasia was observed in all 11 and portal venulopathy in 5 patients. All patients had esophageal varices; 3 developed variceal bleeding. Six patients had ascites; 2 required transjugular intrahepatic portal systemic shunt. Exposure to didanosine and/or a hypercoagulable tendency might predispose patients infected with HIV-1 to vascular changes resulting in NCPH.